Identification of a Shared Cytochrome p4502E1 Epitope Found in Anesthetic Drug-Induced and Viral Hepatitis - Elisa K. McCarthy (American Society for Microbiology, 2018)
ABSTRACT Cytochrome p4502E1 (CYP2E1) autoantibodies are biomarkers for drug-induced hepatitis and chronic hepatitis C. However, major histocompatibility-restricted CYP2E1 epitopes associated with these diseases have not been identified. We hypothesized that CYP2E1 epitopes associated with different types of hepatitis may be shared and may impact immune responses and metabolism. SYFPEITHI epitope prediction identified CYP2E1 candidate epitopes that would be recognized by MHC II haplotypes. Candidate epitopes were tested for induction of hepatitis and CYP2E1 autoantibodies in mice and recognition by sera from patients with anesthetic drug-induced and viral hepatitis. Human liver cells treated with epitope hybridoma serum were analyzed for mitochondrial stress. CYP2E1 activity was measured in human microsomes similarly treated. Epitope antibodies in viral hepatitis sera were analyzed using linear regression to uncover associations with liver pathology. A P value of <0.05 was considered significant. One epitope (Gly113-Leu135) induced hepatitis and CYP2E1 autoantibodies in mice after modification of Lys123 (P < 0.05). Gly113-Leu135 antiserum recognized mitochondria and endoplasmic reticula (P < 0.05), upregulated HSP27 (P < 0.01) and mitochondrial oxidative stress via complex 1 inhibition (P < 0.001), and inhibited CYP2E1 activity. Gly113-Leu135 IgG4 detected in viral hepatitis sera was associated with severe hepatic fibrosis (P = 0.0142). We found a novel CYP2E1 epitope that was detected in anesthetic and viral hepatitis and that triggered hepatitis in mice. Our findings may improve understanding of hepatic immune responses triggered by metabolism or viruses. IMPORTANCE Drug-induced hepatitis is the leading reason that an approved drug is removed from the commercial market. Halogenated anesthetics can induce hepatitis in susceptible persons, and cytochrome p4502E1 (CYP2E1) enzymes responsible for their metabolism induce antibodies in addition to hepatitis. CYP2E1 antibodies detected in anesthetic hepatitis patients have been detected in patients with viral hepatitis, suggesting that these different forms of hepatitis could develop immune reactions to a common segment or epitope of CYP2E1. We have found a common MHC-restricted CYP2E1 epitope in anesthetic and viral hepatitis that is a dominant epitope in anesthetic hepatitis and is significantly associated with fibrosis in patients with viral hepatitis. Along with conformational epitopes, our identification of MHC-restricted CYP2E1 epitopes can be used to develop specific diagnostic tests for drug-induced or viral hepatitis or associated fibrosis or to predict individuals at risk for developing these diseases or their sequelae.